PERLINDUNGAN HUKUM KREDITOR SEPARATIS DALAM RENVOI PROSEDUR TERHADAP BANTAHAN OBJEK AGUNAN YANG TERDAFTAR DI KANTOR PERTANAHAN - Humaltike Kristine; Nur Hakim; Achmad Fitrian (SINERGI : Jurnal Riset Ilmiah, 2026)
The practice of bankruptcy in Indonesia shows that separatist creditors as holders of material security rights on collateral objects registered at the Land Office normatively have a preferred position to execute their guarantees, but in reality the implementation of these rights is often hampered by third party objections through the renvoi procedure mechanism which causes legal uncertainty and delays in execution. Meanwhile, the bankruptcy law system and material security law require certainty, protection, and effectiveness in fulfilling the rights of separatist creditors according to the droit de préférence and droit de suite principles for objects that have been legally registered. The inconsistency between the factual conditions and the normative construction has caused the not optimal regulation and practice of the renvoi settlement procedure for the denial of registered collateral objects, especially related to the limitation of evidence, the protection of land registration certainty, and the guarantee of the certainty of dispute resolution time, so that an in-depth analysis of the form and effectiveness.This research uses normative legal methods with statutory, conceptual, and case approaches. Secondary data consists of primary legal materials such as legislation and court decisions, secondary legal materials including books and scientific journals, and tertiary legal materials. Data collection through library research and analyzed qualitatively using systematic interpretation. The results showed that separatist creditors on collateral belonging to third parties remain as preferred creditors based on the droit de suite principle (Article 7 UUHT), so that the curator's denial that lowers its status to concurrent juridically eliminates the right of independent execution and voting rights guaranteed by law. In this case, the Renvoi procedure becomes a legal protection instrument to correct the curator's actions through proving the validity of the mortgage certificate, as confirmed in Supreme Court Decision No. 689 K / 2012, so that this mechanism serves to restore the material rights of separatist creditors and prevent the unfair distribution of bankruptcy bonds.